Occipitocervical Fusion Surgery: Review of Operative Techniques and Results - Kukreja, Sunil; Ambekar, Sudheer; Sin, Anthony H.; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective Varying types of clinicoradiologic presentations at the craniovertebral junction (CVJ) influence the decision process for occipitocervical fusion (OCF) surgery. We discuss the operative techniques and decision-making process in OCF surgery based on our clinical experience and a literature review.Material and Methods A total of 49 consecutive patients who underwent OCF participated in the study. Sagittal computed tomography images were used to illustrate and measure radiologic parameters. We measured Wackenheim clivus baseline (WCB), clivus-canal angle (CCA), atlantodental distance (ADD), and Powers ratio (PR) in all the patients.Results Clinical improvement on Nurick grading was recorded in 36 patients. Patients with better preoperative status (Nurick grades 1–3) had better functional outcomes after the surgery (p = 0.077). Restoration of WCB, CCA, ADD, and PR parameters following the surgery was noted in 39.2%, 34.6%, 77.4%, and 63.3% of the patients, respectively. Complications included deep wound infections (n = 2), pseudoarthrosis (n = 2), and deaths (n = 4).Conclusion Conventional wire-based constructs are superseded by more rigid screw-based designs. Odontoidectomy is associated with a high incidence of perioperative complications. The advent of newer implants and reduction techniques around the CVJ has obviated the need for this procedure in most patients.
Keywords: occipitocervical fusion; surgical techniques; atlantoaxial instability